Peneguhan Reformasi Birokrasi melalui Penilaian Kinerja Pelayanan Publik - Hayat Hayat (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
This study aims to investigate the implementation of performance appraisal of public services in the Village Cemorokandang as a form of affirmation of bureaucratic reform. This research method using qualitative descriptive through surveys, interviews and distributing questionnaires. The result showed that the implementation of performance appraisal of public services in the Village Cemorokandang was successful. The performance assessment it done using the Sasaran Kerja Pegawai (SKP). SKP has significant impacts on the assessment using such as motivation in the competitive performance, namely as a form of motivation in the competition's performance, an objective in its research and targeted who is rated, control the behavior of employees and enhancements to the character of the civil state apparatus.